A facile direct deposition of silver nanoparticles on silicon surface by silver mirror process. Issue 12 (4th December 2013) - Jiang, Bing; Li, Meicheng; Song, Dandan; Li, Yingfeng; Mwenya, Trevor
<x xml:space="preserve">Abstract</x> Ag nanoplates and Ag polyhedrons are produced on Si surface by controlling the reaction temperature. Ag nanoplates are easily obtained at the low temperature, which are the products controlled by kinetics pathway. Ag polyhedrons are produced at the high temperature under the combined action of the surface energy and strain energy. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>